Seed morphology using SEM techniques for identification of useful grasses in Dera Ghazi Khan, Pakistan. Issue 3 (18th November 2019) - Ahmad, Shafiq; Zafar, Muhammad; Ahmad, Mushtaq; Ali, Muhammad I.; Sultana, Shazia; Rashid, Neelam; Butt, Maryam A.; Shah, Syed N.; Ozdemir, Fethi A.; Kutlu, Mehmet A.; Afza, Rabia; Usma, Anwer; et al.
Abstract: In recent study, 15 taxa of family Poaceae from Dera Ghazi Khan were investigated for morphological characterization of seeds. Scanning electron microscopy (SEM) was utilized to study morphological features of grass seeds. Moreover, economic importance of studied taxa has been discussed in present research. Grass seeds or caryopsis were collected in their mature state from different areas of Dera Ghazi Khan. Collected caryopses were subjected to SEM to investigate surface sculpture, epidermal cell shape, and cell wall patterns. Caryopsis shape observed was elliptic to oval. Also, the morphology of plant is being investigated. Cell wall pattern observed was straight and wavy. Surface sculpturing varies from smooth to reticulate. Epidermal cell shape was either wavy or irregular. Hilum position is terminal in all species. Epidermal cell structure and cell wall pattern was not observable in some species. Major variations among studied taxa were observed in terms of seed surface pattern. Five types of caryopsis surface pattern were observed namely, striate, smooth, reticulate, papillate, and granulate. Investigated taxa illustrated variations in terms of studied morphological features. Utilization of SEM has been proved very helpful in exploring seed morphological features. These observed features can aid in delimitation and identification of various grass taxa. Recent research recommends the utilization of SEM for caryopsis morphology to solve the identification issue of problematic grass genera. Abstract :